A New Class of Quinoline-Based DNA Hypomethylating Agents Reactivates Tumor Suppressor Genes by Blocking DNA Methyltransferase 1 Activity and Inducing Its Degradation - Datta, Jharna (2009)
Reactivation of silenced tumor suppressor genes by 5-azacytidine (Vidaza) and its congener 5-aza-2′-deoxycytidine (decitabine) has provided an alternate approach to cancer therapy. We have shown previously that these drugs selectively and rapidly induce degradation of the maintenance DNA methyltransferase (DNMT) 1 by a proteasomal pathway. Because the toxicity of these compounds is largely due to their incorporation into DNA, it is critical to explore novel, nonnucleoside compounds that can effectively reactivate the silenced genes. Here, we report that a quinoline-based compound, designated SGI-1027, inhibits the activity of DNMT1, DNMT3A, and DNMT3B as well M. SssI with comparable IC(50) (6–13 µ mol/L) by competing with S-adenosylmethionine in the methylation reaction. Treatment of different cancer cell lines with SGI-1027 resulted in selective degradation of DNMT1 with minimal or no effects on DNMT3A and DNMT3B. At a concentration of 2.5 to 5 µmol/L (similar to that of decitabine), complete degradation of DNMT1 protein was achieved within 24 h without significantly affecting its mRNA level. MG132 blocked SGI-1027–induced depletion of DNMT1, indicating the involvement of proteasomal pathway. Prolonged treatment of RKO cells with SGI-1027 led to demethylation and reexpression of the silenced tumor suppressor genes P16, MLH1, and TIMP3. Further, this compound did not exhibit significant toxicity in a rat hepatoma (H4IIE) cell line. This study provides a novel class of DNA hypomethylating agents that have the potential for use in epigenetic cancer therapy.